Treatment of dentine hypersensitivity by lasers: a review - Kimura, Yuichi; Wilder-Smith, Petra; Yonaga, Kazuo; Matsumoto, Koukichi (Journal of clinical periodontology, 2000)
Background, aims: Since the development of the ruby laser by Maiman in 1960, a variety of papers on potential applications for lasers in dentistry have been published. The purpose of this paper is to summarise laser applications for the treatment of dentine hypersensitivity. The effects of laser on pulp tissue and problems on laser treatment are also reviewed. This article reviews the role of lasers for the treatment of dentine hypersensitivity since 1985, summarises many research reports from the last decade, and surmises what the future may hold for lasers in this treatment. Method: To date, 4 kinds of lasers have been used for the treatment of dentine hypersensitivity, and the effectiveness ranged from 5.2 to 100%, which was dependent on the laser type and parameters used. The mechanism involved in laser treatment of dentine hypersensitivity are relatively unknown. Results: These require clarification to result in safely effective treatment optimization. In general, the efficiency for the treatment of dentine hypersensitivity using lasers is higher than other methods, but in severe cases, it is less effective. Conclusion: It is necessary to consider the severity of dentine hypersensitivity before laser use.